COVID-19 vaccination, risk-compensatory behaviours, and contacts in the UK - John Buckell; Joel Jones; Philippa C. Matthews; Sir Ian Diamond; Emma Rourke; Ruth Studley; Duncan Cook; Ann Sarah Walker; Koen B. Pouwels; the COVID-19 Infection Survey Team (Scientific Reports, 2023)
Abstract The physiological effects of vaccination against SARS-CoV-2 (COVID-19) are well documented, yet the behavioural effects not well known. Risk compensation suggests that gains in personal safety, as a result of vaccination, are offset by increases in risky behaviour, such as socialising, commuting and working outside the home. This is potentially important because transmission of SARS-CoV-2 is driven by contacts, which could be amplified by vaccine-related risk compensation. Here, we show that behaviours were overall unrelated to personal vaccination, but—adjusting for variation in mitigation policies—were responsive to the level of vaccination in the wider population: individuals in the UK were risk compensating when rates of vaccination were rising. This effect was observed across four nations of the UK, each of which varied policies autonomously.